Determinants of Sweet Corn Productivity and Its Impact on Farmers' Welfare in Curup Selatan District, Rejang Lebong Regency, Indonesia - Sunandar Sunandar; Putri Ayu Maharani; Indah Mutiara Fadhillah; Elni Mutmainnah; Putri Mian Hairani (AGRITROPICA : Journal of Agricultural Sciences, 2026)
Sweet corn (Zea mays saccharata Sturt.) is a horticultural commodity with high market demand, yet its productivity at the farmer level remains variable. This study aimed to assess sweet corn productivity and analyse factors associated with yield and farmer economic welfare in Curup Selatan District, Rejang Lebong Regency, Bengkulu Province, Indonesia. The study was conducted in March 2026, using purposive sampling, with 42 sweet corn farmers. Primary data were collected through structured interviews and analysed using validity and reliability tests, followed by Partial Least Squares–Structural Equation Modelling(PLS-SEM). The results showed that the average sweet corn yield was 8.21 tons ha⁻¹. Farmers perceived seed quality and soil condition as the main factors associated with sweet corn productivity. The PLS-SEM model explained 68.5% of the variation in yield and 84.7% of the variation in farmers' economic welfare. Yield had a positive and significant effect on farmer economic welfare, while landholding characteristics and cultivation techniques had positive and significant effects on sweet corn yield. Farming constraints and planting period did not significantly affect yield. These findings indicate that improving seed quality, soil management, and cultivation practices should be prioritised to enhance sweet corn productivity and farmer economic welfare.